Wound Healing Activity of 80% Methanolic Crude Extract and Solvent Fractions of the Leaves of Justicia schimperiana (Hochst. ex Nees) T. Anderson (Acanthaceae) in Mice - G/giorgis SG; Ambikar D; Tsegaw A; Belayneh YM (Dove Medical Press, 2022)
Shemelis Gebrewoled G/giorgis,1 Digambar Ambikar,2 Asegedech Tsegaw,2 Yaschilal Muche Belayneh3 1Department of Pharmacy, Dessie Health Science College, Dessie, Ethiopia; 2Department of Pharmacology, School of Pharmacy, College of Medicine and Health Sciences, University of Gondar, Gondar, Ethiopia; 3Department of Pharmacy, College of Medicine and Health Sciences, Wollo University, Dessie, EthiopiaCorrespondence: Yaschilal Muche Belayneh, Department of Pharmacy, College of Medicine and Health Sciences, Wollo University, P.O. Box, 1145, Dessie, Ethiopia, Tel +251 918092466, Email yaschilal.muche19@gmail.comIntroduction: Justicia schimperiana has been used traditionally for the treatment of wound and skin burn, but there is no scientific evidence that supports the traditional claim.Objective: To evaluate the wound healing activity of 80% methanol crude extract and solvent fractions of the leaves of Justicia schimperiana in mice.Methods: Mice were used for wound healing study, while rats were used for acute dermal toxicity test. The 80% methanol crude extract and chloroform, ethyl acetate and aqueous fractions were formulated in ointments with 5% and 10% strength. Burn, excision and incision wound models were used to evaluate the effect of the crude extract, whereas the activity of the solvent fractions was evaluated using excision wound model. Parameters such as wound contraction, and period of epithelialization were studied in the excision and burn wound models, while tensile strength was measured in incision wound model.Results: Treatment of wound with 80% methanol extract of Justicia schimperiana leaves using 5% (w/w) and 10% (w/w) ointment formulation induced significant (P< 0.05) improvement in wound contraction rate, epithelialization time and skin breaking strength in excision, incision and burn wound model, respectively as compared to negative control. The chloroform, ethyl acetate and aqueous fractions with 5% (w/w) and 10% (w/w) ointment formulation showed significant (p< 0.001) improvement in wound contraction and epithelialization time in excision wound model as compared to the negative control group.Conclusion: This study has demonstrated that the 80% methanol crude extract and solvent fractions of Justicia schimperiana leaves possess wound healing activity.Keywords: Justicia schimperiana, wound, wound healing